Chronic kidney disease, worsening renal function and outcomes in a heart failure community setting: A UK national study. (15th September 2018) - Lawson, Claire A.; Testani, J.M.; Mamas, M.; Damman, K.; Jones, P.W.; Teece, L.; Kadam, U.T.
Abstract: Background: Routine heart failure (HF) monitoring and management is in the community but the natural course of worsening renal function (WRF) and its influence on HF prognosis is unknown. We investigated the influence of routinely monitored renal decline and related comorbidities on imminent hospitalisation and death in the HF community population. Methods: A nested case-control study within an incident HF cohort ( N = 50, 114) with 12-years follow-up. WRF over 6-months before first hospitalisation and 12-months before death was defined by >20% reduction in estimated glomerular filtration rate (eGFR). Additive interactions between chronic kidney disease (CKD) and comorbidities were investigated. Results: Prevalence of CKD (eGFR<60 ml/min/1.73m 2 ) in the HF community was 63%, which was associated with an 11% increase in hospitalisation and 17% in mortality. Both risk associations were significantly worse in the presence of diabetes. Compared to HF patients with eGFR, 60–89, there was no or minimal increase in risk for mild to moderate CKD (eGFR, 30–59) for both outcomes. Adjusted risk estimates for hospitalisation were increased only for severe CKD(eGFR, 15–29); Odds Ratio 1.49 (95%CI;1.36, 1.62) and renal failure(eGFR, <15); 3.38(2.67, 4.29). The relationship between eGFR and mortality was U-shaped; eGFR, ≥90; 1.32(1.17, 1.48), eGFR, 15–29; 1.68(1.58, 1.79) and eGFR, <15; 3.04(2.71, 3.41). WRF is common and associated with imminent hospitalisation (1.50;1.37, 1.64) and mortality (1.92;1.79, 2.06). Conclusions: In HF, the risk associated with CKD differs between the community and the acute HF setting. In the community setting, moderate CKD confers no risk but severe CKD, WRF or CKD with other comorbidities identifies patients at high risk of imminent hospitalisation and death. Highlights: The study was based on 50, 114 heart failure patients from UK general practices. Risk associated with CKD in the community is limited to the severest dysfunction. CKD interacts with diabetes, significantly worsening outcome risk. WRF is associated with high risk of imminent hospitalisation or mortality. Routine renal function monitoring in the community offers a simple prognostic tool.